(untitled) (Journal of Computational Mathematics, 1994)
In this paper we are concerned with the modified conjugate direction method for computing the pseudoinverse by using an orthogonal basis of the range space of A. Numerical results show that the new method retains some main advantages in terms of efficiency and accuracy.